A self adaptive hybrid differential evolution algorithm for phase balancing of unbalanced distribution system - Sathiskumar, M.; Nirmal kumar, A.; Lakshminarasimman, L.; Thiruvenkadam, S. (International journal of electrical power & energy systems, 2012)
► This paper proposes a SaHDE method to find the optimal phase movement among phases. ► The primary objective of phase balancing is to balance the loads with the phases. ► This paper introduces SaHDE which self tunes control parameters of DE technique. ► SaHDE has fast convergence characteristics and simple in implementation. ► The Proposed method was tested successfully On IEEE 34 Nodes and IEEE 123 Nodes. Electrical power distribution systems are critical links between the utility and customer. In general, power distribution systems have unbalanced feeders due to the unbalanced loading. The devices that dependent on balanced three phase supply are affected by the unbalanced feeders. This necessitates the balancing of feeders. Phase swapping, the process of changing the loads amongst phases, has been practiced for feeder phase balancing. The primary objective of phase balancing is to balance the loads with the phases subject to constraints such as load flow equations, capacity and voltage constraints, while maintaining the radial structure. In this paper, a Self adaptive Hybrid Differential Evolution (SaHDE) technique has been employed to solve the phase balancing problem. The effectiveness of the proposed method is demonstrated through modified IEEE 34 node and IEEE 123 node distribution systems.